Ownership authentication by digital image watermarking based on block truncation coding - Tohidi, Faranak (2013)
Image authentication methods have recently gained great consideration due to their importance for a huge number of multimedia applications. Digital images are increasingly conveyed over vulnerable channels such as the Internet. Protecting digital product is going to become important issue to ensure the secure transmission of the digital items. The existing algorithms cannot guarantee the whole security of the contents or ownership verification. The embedded watermark or data hiding into image can be used to identify the owner of the image. Also, The Block Truncation Coding (BTC) is one of the effective and real time application for data hiding. Most present BTC based watermarking methods cannot completely exploit visual perception of the cover images and do not obtain high data embedding rate. For more exploiting visual perception and high data embedding, an enhanced data hiding scheme based on BTC is proposed. In proposed method, considering the texture sub blocks and Least Significant Bits (LSBs of higher mean value and lower mean value) substitution combine together for designing improved the BTC watermarking scheme. It can obtain good balance between high embedding rate (capacity) and high quality. So, the texture sensitivity is exploited to recognize whether the image blocks or are smooth or complex. On the other hand, the LSB substitution method is employed to hide the indicator bits of each image block or sub block. The experimental results show that the proposed method increases capacity of data hiding compare to existing BTC watermarking with the same or higher quality.